Corporate finance - Ross, Stephen A.; Jaffe, Jeffrey F.; Westerfield, Randolph (Chicago : Irwin, 1996)
With an emphasis on the fundamentals of finance theory, this text uses the intuitions of arbitrage, net present value, efficient markets and options to present corporate finance as the working of a small number of integrated and powerful intuitions. This edition includes expanded "Problem Sets".
Includes bibliographical references and indexes.
oif 26/03/15
Loan
Keywords: Corporations; Corporations; Entreprises